Computerised Stress -Test: Usual or New Derivative Electrocardiographic Variables - Bertašienė, Z.; Blužas, J.; Braždžionytė, J.; Vainoras, A.; Žaliūnas, R. (Elektronika ir Elektrotechnika, 2004)
For better prediction ischemic heart disease (IHD) and coronary artery stenoses 35 healthy women and 90 women with IHDhospitalised at Kaunas medical university hospital undergone veloergometry by means of computerised system “Kaunas-Krūvis”.Calculated variable - ST and JT product at the maximum load - has stronger correlation with IHD and three-vessel disease than routinevariable – ST depression greater than 0,1 mV. The value of ST and JT product at the peak of exercise >10,3 mVms with 88% sensitivityand 94% specificity predicts IHD in women. The most accurate predictors of three-vessel disease in women with IHD were ST and JTproduct and JT dispersion at the peak of exercise, and the fact of previous MI. Ill. 2, bibl. 8 (in English; summaries in Lithuanian,English and Russian).